SYSTEMATICS AND IDENTITY OF FOUR PELAGIC SHARKS OF THE FAMILY CARCHARHINIDAE FROM INDIAN REGION - Nair, R V; Appukkuttan, K K; Rajapandian, M E (Indian Journal of Fisheries, 2011)
Four species of pelagic sharks of the family Carcharhinidae belonging tothe genera ScoUodon, Loxodon and Rhizoprionodon viz., ScoUodon laticauJusMuUer and Henle, Loxodon macrorhinus MuUer and Henle, Rhizoprionodon(Rhizoprionodon) acutus RuppeJl and Rhizoprionodon (Protozygaena) oUgoUnxSpringer which constitute a good fishery along the west and southeast coasts ofIndia are described. Since there is confusion about the systematic position andidentity of these species, an attempt is made to give detailed description of allthe four species collected from different centres of both the coasts.